Patterns of sexual behavior in lowland Thai youth and ethnic minorities attending high school in rural Chiang Mai, Thailand - Aurpibul L. (2017)
© 2016 Aurpibul et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Introduction: The rural areas of Northern Thailand are home to a large cultural diversity of ethnic minority groups. Previous studies have shown that young people in rural Thailand have low levels of knowledge on HIV/AIDS and high sexual risks. We compared sexual behaviors between the lowland Thai youth and the youth from ethnic minority groups. Methods and findings: This is a cross-sectional quantitative study conducted among high-school Thai and ethnic students in Chiang Mai. From a total 1215 participants, 487 (40.1%) were lowland Thai and 728 (59.9%) were from ethnic minorities. Overall, 17.9% of respondents reported "ever had sex." Lowland Thai adolescents were more likely to have ever had sex compared with ethnic minority adolescents (AOR, 1.61; CI, 1.06±2.45; P < 0.01). A higher proportion of lowland Thai respondents reported having ≥ 2 lifetime sexual partners (51.9% vs. 33.3%, P = 0.003), or currently having a boy/girlfriend (59.9% vs. 45.3%, P < 0.001) compared to ethnic minority adolescents. Consistent condom use was low in both groups (22.6%). The common significant factors associated with "ever had sex" in both groups were "ever drunk alcohol in the past year" and "currently having a boy/girlfriend." Specifically, for lowland Thai youth, being around the age of 17 or 18 years and "ever used methamphetamine in the past year" were associated with increased odds of "ever had sex". For ethnic minority adolescents, being female and belonging to religions other than Buddhism were associated with decreased odds of "ever had sex". Conclusion: A substantially higher proportion of lowland Thai engage in risky sexual behaviors when compared to ethnic minorities. However, both groups remained vulnerable to HIV and other sexually transmitted infections. To minimize sexual risks, education program and school-based interventions are warranted to increase awareness of young people about risky behaviors and to promote essential life skills.